The impact of second-generation androgen receptor pathway inhibitors on skeletal muscle morphology and strategies to mitigate their effects in prostate cancer patients - Edwards, Sarah; Lulic-Kuryllo, Tea; Batra, Anupam (Frontiers in Rehabilitation Sciences, 2025)
The standard of care for metastatic castrate sensitive prostate cancer (mCSPC) involves the use of doublet therapies, which prolong survival and delay disease progression. Doublet therapies include the addition of second-generation androgen receptor pathway inhibitors (ARPIs) to androgen deprivation therapy (ADT). ADT monotherapy has been associated with adverse effects on skeletal muscle morphology, muscle strength, and physical function. Our findings suggest that the addition of ARPIs to ADT may further exacerbate these adverse effects. This review provides an overview of the current evidence to initiate exercise during treatment as an intervention to mitigate these adverse effects. Despite growing research in exercise oncology, research on the effects of exercise in men with mCSPC treated with doublet therapy is lacking. Much of the current supporting evidence is based on men with metastatic castrate resistant prostate cancer. Nonetheless, this review examines the available research on the efficacy and benefits of participating in a regimented exercise program in men with metastatic prostate cancer. We highlight the emerging evidence that exercising during treatment has the potential to protect against the adverse effects of doublet therapy. Future research to uncover the effects of different doublet therapies on muscle health in mCSPC is needed. Moreover, an improved understanding of the optimal training dose and timing that would elicit the most optimal benefits on muscle health in men with mCSPC is required.